Elements of Vandalism in Law Number 1 of 2023 Concerning the Criminal Code - Murshal Senjaya (East Asian Journal of Multidisciplinary Research, 2023)
The element of vandalism in Law Number 1 of 2023 concerning the Criminal Code, vandalism is included in the form of delinquency. Crimes related to delinquency are regulated in Article 331. In this article, it is explained that perpetrators of delinquency can be punished with category II fines or as much as IDR 10 million. "Any person who in a public place commits delinquency against people or goods that can cause harm, loss or distress, shall be punished with a maximum fine of category II," reads Article 331. In the explanation section, the example of delinquency in question is scribbling wall on a public street. The factors that cause vandalism are users, factors from the library, other factors including the environment, stress and communication blockages. The effort to deal with vandalism is the need for an intellectual mentality of users so they don't vandalize a collection of library materials. Attitudes and behavior of librarians/library officers who always control users both in the room and the exit. For certain types of collections, closed access services can be performed. Make written rules and clear sanctions for those who commit violations. Controlling the use of manual and automated membership cards so that they do not use other people's membership cards. The entrance is always closed, only users who have a card can enter the library.